Literature Review: Strategi Promosi Rokok Versus Strategi Promosi Kesehatan Anti Rokok - Havizoh, Havizoh; Widyatuti, Widyatuti (Jurnal Kesehatan, 2020)
Globally, the amount of loss due to smoking has been well documented. But smoking among teenagers not only dwells on the problem of physical danger in the form of illness or death but also damages emotions and behavior. The phenomenon of smoking among adolescents takes attention because the future of a nation is determined by the quality of its future generations. This paper focuses on understanding cigarette promotion strategies and juxtaposing them with anti-smoking health promotion strategies with the literature review method. The results show that there are gaps in themes and content where health promotion strategies are considered rigid and have not yet adapted to the development of millennial adolescents. The recommendations given should be that themes and content in health promotion be packaged more interactively and flexibly according to the current era. Incorporating elements of anti-smoking health promotion into the game features will allow health promotion to be more acceptable among teenagers.